Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Pada Harum Sari Butik Gianyar - Wulandari, Ni Kadek; Wijaya, Putu Yudy; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the influence of price, product quality and service quality on consumer purchasing decisions at Harum Sari Butik. The population in this research is consumers who buy kebaya at Harum Sari Butik with a sample size of 90 respondents who were determined using the purposive sampling method. Data collection was carried out through observation, interviews, documentation, literature study, questionnaires. The data analysis technique used in this research is multiple linear regression analysis technique. Based on the research results, it can be seen that: Price has a partially positive and significant effect on purchasing decisions. Product quality has a partial positive and significant effect on purchasing decisions. Service quality partially influences purchasing decisions. Price, Product Quality and Service Quality have a positive and significant effect on Purchasing Decisions. Looking at the research results, in the future Harum Sari Butik must adjust the price of each product offered, ensuring that the price of each product from Harum Sari Butik is adjusted to the quality of the product offered both in terms of model or type of fabric of the product so that consumers feel that the price of the product is too expensive and causes a decrease in purchasing decisions